Palmyra and coconut haustorium: A comprehensive review on nutritional composition, bioactive potential, value-added products and its health benefits - Raja Rajeshwari E; Sathanya P S; Vignesh S; Baskaran N (Food Chemistry Advances)
The various parts of the palmyra and coconut trees which are widely distributed in the southern parts of the Indian subcontinent have been studied and utilized for many years. These contain a white and spongy edible component in them which is found during the germination of the seeds called haustorium. The palmyra and coconut trees each have different sections with special medical properties. Recently, the haustorium of both coconut and palmyra trees has been gaining increased attention from researchers due to its nutritional properties. Certain studies on the haustoria have revealed the presence of various compounds that are beneficial for human health. The bioactive compounds found in the previous studies include phenols, flavonoids, terpenoids, pyrimidine groups and certain vitamins which act as antioxidant, anti-inflammatory, anti-ulcer, anti-diabetic, anti-cancer, and anti-mutagenic agents. This review focuses on comparing the nutritional composition, bioactive compounds, sugar profile fatty acid profile, amino acid profile, minerals, and vitamins of both palmyra and coconut haustorium. This review also reports on the value addition of the haustoria as usually they are consumed in their raw form. These value-added products not only enhance the economic viability of these underutilized resources but also contribute to extending their shelf life, making them more accessible in the market. Also, this review emphasizes the haustorium's potential defence against negative consequences. Therefore, this review paper helps in understanding the palmyra and coconut haustorium and its potential health benefits.